The Effect of Project-Based Learning (PBL) on Lessons Written in The Second Grade of SMPN 1 Parepare - Mujahidah; Anita Anggerani; Wahyu Hidayat; Yulie Asni (Inspiring: English Education Journal, 2022)
Anita Anggreani, The Effect of Project Based Learning (PBL) in Teaching Writing to the Second Grade of SMPN 1 Parepare, (Supervised by Mujahidah and Wahyu Hidayat.) Project Based Learning (PBL) is a learning model in which students work individually to produce a particular product that originates from the problems that surround it. The goal of this study is to describe how students learn English in class VIII.2 of SMPN 1 Parepare using Project Based Learning (PBL) strategy, as well as to determine whether students’ writing ability in learning English increases as a result of the Project Based Learning (PBL) strategy. This research is a classroom action research that attempts to improve students’ writing abilities in English learning through a Project Based Learning strategy. The subjects were 32 students from SMPN 1 Parepare class VIII.2 during the academic year 2021/2022. The research was split into two cycle. The information for this research was acquired thorugh an interview, an observation checklist, a questionnaire, and a test. The study’s fidings revealed that students’ English skills improved as evidenced by: a) the percentage of students steadily improved their scores at the conclusion of each cycle. The English lesson’s Minimum Mastery Criterion-Kriteria Ketuntasan Minimal (KKM) Score was 78 (Seventy Five). The students average pre-test score was 58,9. In the first cycle, the average score was 76,6. In the second cycle, the average score was 86,3. b) The students’ responses to the increased interest in learning English through a Project Based Learning (PBL) strategy are generally positive. The data showed a score of 94,3%, which means “Excellent”. c) through an observation checklist, students’ participation in students activities indicating that students’ participation steadily increased form the first to the second cycle. Keywords: Project based learning, Writing ability, Descriptive text